Răspuns :
=5(a-b+1)
4x patrat-49=(2x-7)(2x+7), unde folosim diferenta de patrate: a la puterea a doua -b la a doua= (a-b)(a+b)
4x patrat-49=(2x-7)(2x+7), unde folosim diferenta de patrate: a la puterea a doua -b la a doua= (a-b)(a+b)
a)5a-5b+5 = 5(a-b)+5 = 5(a-b+1)
b)[tex] 4x^{2} [/tex] -49 = (2x-7)(2x+7) Conform formulei de calcul prescurtat =>>[tex] x^{2} [/tex] - [tex] y^{2} [/tex] = (x-y)(x+y)
b)[tex] 4x^{2} [/tex] -49 = (2x-7)(2x+7) Conform formulei de calcul prescurtat =>>[tex] x^{2} [/tex] - [tex] y^{2} [/tex] = (x-y)(x+y)